2007
DOI: 10.1111/j.1467-6494.2006.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Coaching Behaviors Associated With Changes in Fear of Failure: Changes in Self‐Talk and Need Satisfaction as Potential Mechanisms

Abstract: Cognitive-interpersonal and motivational mechanisms may regulate relations between youth perceptions of interpersonal aspects of the social ecology and their fear-of-failure (FF) levels. Youth (N=165) registered for a summer swim league rated their fear of failure at the beginning, middle, and end of the season. Extensive model comparisons indicated that youths' end-of-season ratings of coach behaviors could be reduced to three factors (affiliation, control, blame). Perceived control and blame from coaches pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…that coach esteem, support, and behaviors are related to athletes' use of self-talk such that supportive coaching behaviors are associated with more positive and less negative self-talk in athletes and negative coaching behaviors such as high levels of perceived control and blame are related to athlete use of negative self-talk (Conroy & Coatsworth, 2007;Conroy & Pincus, 2006: Theodorakis et al, 2012Zourbanos et al, 2011). Much of the research that has been conducted in sport contexts is correlational.…”
Section: Self-talk: Review and Sport-specific Model Of Self-talk 23mentioning
confidence: 93%
See 1 more Smart Citation
“…that coach esteem, support, and behaviors are related to athletes' use of self-talk such that supportive coaching behaviors are associated with more positive and less negative self-talk in athletes and negative coaching behaviors such as high levels of perceived control and blame are related to athlete use of negative self-talk (Conroy & Coatsworth, 2007;Conroy & Pincus, 2006: Theodorakis et al, 2012Zourbanos et al, 2011). Much of the research that has been conducted in sport contexts is correlational.…”
Section: Self-talk: Review and Sport-specific Model Of Self-talk 23mentioning
confidence: 93%
“…For example, little attention has been paid to self-compassionate (e.g., "All humans fail sometimes") self-talk (Mosewich, Crocker, Kowalski, & DeLongis, 2013), calming (e.g., "Be cool and keep playing") self-talk (Schüler & Langens, 2007), self-protective (e.g., "I coach myself in a friendly way) selftalk (Conroy & Coatsworth, 2007), task-irrelevant (e.g., "I want a strawberry milkshake!") selftalk (Berk, 1986), humorous self-talk, self-talk related to enjoyment/appreciation of the moment (e.g., "it is exciting to be in the championship match"), and self-talk related to others, such as "this referee is terrible," "my teammates are playing well," and "my coach will be angry if this continues."…”
Section: Self-talkmentioning
confidence: 99%
“…Coaches and parents appeared to dominate the authority climate, but the influence of parents reduces significantly between the specialisation and investment-mastery stages (e.g. Reeve et al 2002, Vazou et al 2005, Conroy and Coatsworth 2007a, 2007b, Garcia Bengoechea and Strean 2007, Gould et al 2008, Holt et al 2008, Fraser-Thomas and Côté 2009, Keegan et al 2009, 2010b, in press, Gearity and Murray 2011.…”
Section: Authority Climatementioning
confidence: 99%
“…It was broadly broken down into positive reactions (e.g. Conroy and Coatsworth 2007b), tolerant reactions and negative reactions (e.g. Vazou et al 2005, Keegan 2010b, with athletes also referring to 'emotional intensity' of the protagonist, as well as the 'emotional range' of the coach -reflecting the ability to be calm, passionate, or measured in relation to the moment and situational demands (Keegan et al in press).…”
Section: Emotional Climatementioning
confidence: 99%
“…In regard to our sample, this discrepancy might be explained by the fact that females also showed lower values in self-esteem which is negatively associated with fear of failure (30) and considered to be the most frequently aversive consequence (31). Additionally, Conroy and Coatsworth (32) found that self-blame predicted the extent of fear of failure in adolescent athletes. Another explanation could be found in the different sources from which males and females derive their self-esteem.…”
Section: Discussionmentioning
confidence: 99%